Effects of B9 and B12 vitamins deficiency on the genesis of megaloblastic anemia - Karen Aracelly Tobar Armendariz; Silvia Tatiana Tite Andi (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Megaloblastic anemia belongs to the subgroup of deficiency anemias. With the objective of describing the effect of B9 and B12 vitamins deficiency on the genesis of megaloblastic anemia, this research was carried out. Megaloblastic anemia occurs when the levels of folic acid (Vitamin B9) and cyanocobalamin (vitamin B12) are low, thus generating a decrease in the cellular capacity to synthesize deoxyribonucleic acid, which causes hematological alterations in all cell lines of the marrow bone (erythrocytes and platelets), mainly causing the generation of large red blood cells with low hemoglobin concentration. Vitamins B9 and B12 participate in the normal synthesis of nucleic acids, being directly involved in the synthesis of purines and pyrimidines, as well as cell maturation. The deficiency of these vitamins has an effect on the central nervous system functioning.